Türkiye'nin Farklı Derece-gün Bölgelerinde Yer Alacak Örnek Bir Konut İçin Uygun Mekanik Tesisat Sisteminin Tayini - Evren, Arslaner, Mustafa (Enerji Enstitüsü, 2018)
Dünya nüfusunun artması ve insanların refah seviyelerinin değişmesi sonucu enerji ihtiyacı her geçen yıl artış göstermektedir. Uzun dönem, artan enerji ihtiyacı tükenebilir kaynaklardan ve fosil yakıtlardan karşılanmış, bunun sonucunda atmosfere yapılan yoğun karbon emisyonuyla ekosisteme ciddi zararlar verilerek insanoğlu küresel ısınma tehdidiyle karşı karşıya kalmıştır. Bu durum dünyada enerji politikalarının gözden geçirilmesine neden olmuş, tüm ülkeleri enerji tasarrufu ve enerjiyi verimli kullanmaya dair tedbirler almaya mecbur kılmıştır. Gerek dünyada gerekse ülkemizde insanların yaşam alanlarını oluşturan binalar en önemli enerji tüketen kalemler arasında yer almaktadır. Ülkemizde son yıllarda hızlı bir gelişim gösteren inşaat sektörü kapsamında, büyük şehirler başta olmak üzere bir çok şehirde konut inşaatı sayısı artış göstermiştir. Farklı bölgelerde hızla yapılan konutlarda gerekli enerji tasarrufu ve verimliliği tedbirleri düşünülerek, sürdürülebilir yapılar yapılmasına yoğunlaşıldığında önemli ölçüde enerji tasarrufu sağlanarak ülkemizin enerjide dışa bağımlılığı azaltılabilecektir. Yapının sürdürülebilirliğinde en önemli paremetrelerden birisi uygun mekanik tesisat sisteminin seçilmesidir. Mimari anlamda enerji verimli stratejilerin uygulanması tek başına yeterli olamayacağı için mimariye ve iklime uygun mekanik tesisat sisteminin belirlenmesi, yapının sürdürülebilirliğinde pay sahibi olup, önemli ölçüde enerji tasarrufu elde edilmesini sağlayacaktır. Tez çalışmasında, Türkiye'nin beş derece-gün iklim bölgesi için seçilen örnek bir konutta uygun mekanik tesisat sisteminin tayini saatlik simülasyon programı ile irdelenmiştir. Bu kapsamda ele alınan konut, beş iklim bölgesinde standartlarca belirlenen minimum bina kabuğu şartlarını sağlayacak şekilde modellenip ısıtma, soğutma ve kullanım sıcak suyu hazırlanması işlemlerinde kullanılmak üzere üç farklı mekanik tesisat sisteminin yıllık enerji tüketimleri, yıllık CO2 emisyonları ve geri dönüş süreleri her iklim bölgesi için hesaplanıp karşılaştırılmıştır. Bina modellemesi simülasyon programında yapılarak, tüm bina elemanları, iç kazançlar ve aydınlatma yükleri programa tanımlanmıştır. Simülasyonlarda incelenen mekanik tesisat sistemlerinden, referans olarak alınan sistemde ısıtma ve kullanım sıcak suyu ihtiyacının duvar tipi kombi ile, soğutma ihtiyacının ise multi split klima ile karşılandığı düşünülmüştür. Bu sistemlere alternatif olarak ısıtma, soğutma ve kullanım sıcak suyu ihtiyacını karşılamak üzere hava kaynaklı ve yatay serme toprak kaynaklı ısı pompalarının yıllık enerji tüketimleri simülasyon programıyla hesaplanmıştır. Hesaplamalar sırasında, hava kaynaklı ısı pompasının farklı dış hava sıcaklıklarında ve kısmi kapasitelerdeki elektrik tüketimleri ile, toprak kaynaklı ısı pompasının toprak devresinde farklı mevsimlerde oluşan farklı su giriş sıcaklıklarında ve kısmi kapasitelerde elektrik tüketim verileri programa işlenmiştir. Hesaplanan enerji tüketimlerinden yola çıkılarak, birim tüketilen enerji başına atmosfere salınan CO2 miktarı Excel programına işlenerek, karşılaştırılan iklimlendirme sistemlerinin her derece-gün bölgesinde yıllık CO2 emisyonları hesaplanmıştır. Mekanik tesisat sistemlerinin her bölgedeki yıllık enerji faturaları, tüketilen enerjinin birim maliyetinin simülasyon programına işlenmesi sonucu simülasyon programının çıktısı olarak elde edilmiştir. Simülasyonlar sonucunda beşinci iklim bölgesi dışındaki tüm bölgelerde ısı pompası alternatiflerinin ikisi de binanın yıllık enerji harcamalarını ve CO2 emisyonlarını önemli ölçüde düşürmüştür. Geri ödeme süreleri düşünüldüğünde birinci ve ikinci iklim bölgelerinde hava kaynaklı ısı pompası referans iklimlendirme sistemine alternatif olarak kullanılabilmektedir. Üçüncü iklim bölgesinde, hava kaynaklı ve toprak kaynaklı ısı pompalarının geri ödeme süreleri birbirine yakın olduğundan, enerji tüketimi ve CO2 emisyonlarında toprak kaynaklı ısı pompası daha büyük oranda bir düşüş sağladığı için üçüncü bölgede toprak kaynaklı ısı pompası daha iyi bir alternatif olarak göze çarpmaktadır. Dördüncü ve beşinci iklim bölgelerinde ısı pompası sistemlerinin geri ödeme süreleri yüksek olduğundan söz konusu sistemlerin bu bölgelerde ekonomik bir çözüm olmadıkları tayin edilmiştir.

Energy demand in the world increases continuously due to the population rise and prosperity level change of the people. Especially after the industrial revolution and new technological improvements, energy demand has risen rapidly and people have met this demand from limited fossil fuels for a long time. However this strategy damaged the ecosystem and nature significantly by means of high amount of carbon emissions to the atmosphere and as a result of this, global warming became a huge problem for humanity. Consequently, many countries started take significant energy efficiency measures to decrease energy consumption and increase energy efficiency. One of the most energy consuming sector in the world are buildings. In many countries, special precautions are taken and significant legislative regulations are gone into operation to decrease energy consumption and increase sustainability in buildings sector. In addition, many countries started to give incentives to people who considers to use renewable energy strategies in their buildings. In Turkey, construction sector has expanded rapidly in the last few years. Many new buildings are constructed especially in the big cities and large portion of them are built as residentials. So, desiging and constructing these new buildings by considering energy efficiency and sustainability, may create significant decrease in energy consumption and by this way external dependence of our country in terms of energy may become lower. Sustainability is mixture of different parameters which are related with architecture, mechanical and electrical systems and building material. It is such a concept that starts from buildng design and continues until the building ceases to live. The design, is one of the most important stage sustainable buildings because huge portion of energy efficient measures can be taken at this stage with considering several alternatives by all disciplines. Especially for mechanical system identification, engineers analyze different kinds of mechanical system depending on architecture and climatic conditions. Thus all alternative mechanical system cannot be gauged experimentally because of the lack of time and high costs, energy simulation softwares are good solutions for engineers to identify optimum mechanical systems. As the building modeled architecturally into the simulation tool, weather data and building envelope properties are entered into the program. The more detailed information entered to the simulation tool, the more realistic results can be obtained. Thus, mechanical systems have a significant portion of energy consumption. Architectural measures cannot be enough by itself to construct sustainable buildings. By choosing suitable mechanical system for a building, energy consumption and CO2 emissions of the buildings can be decreased significantly. In the scope of this thesis, an optimum mechanical system is aimed to be identified in a residential building for five degree-day zones of Turkey. In these climate zones, first one can be considered as the hottest one and the fifth one can be considered as the coldest one. From one to five, climate zones' heating degree days become higher and cooling degree days become lower. The building is consist of 50 m2 and 3,5 meter height. Two people, both of them work in weekdays, were considered to be lived in this building. Thermal properties of building envelope is determined by the minimum Turkish Standard requirement. One representative city is chosen for each climate zone. Izmir, Istanbul and Ankara are selected representative cities for respectively first,second and third climate regions. The reason to be choosen these cities for first three region is, design and simulation weather informations were included automatically in simulation programme for these three cities. Van and Erzurum are selected to represent the fourth and fifth climate regions respectively. However, thus the simulation program does not include the climatic informations of these cities, cities that included in program databese and having similar climatic characteristics were taken into consideration. The similarity of these cities were identified by taking the cities that are in the same climatic region with Van and Erzurum according to Köppen Geiger Climate Classification. Idaho Twin Falls' climatic datas are taken for Van and Moscow's climatic datas are taken for Erzurum. Three different mechanical system has been analyzed and hourly simulated for five different climate zones. These mechanical systems were compared by means of energy consumptions, energy bills, CO2 emission and payback periods. For baseline mechanical system, heating demand is met by wall mounted condensing combi boiler, cooling demand is met by multi split air conditioning system. Two types of heat pump systems; air source heat pump and horizontal type ground source heat pump are modeled in the simulation program and compared with baseline mechanical systems. For air source heat pump, electrical consumptions in partial loads and for different air temperatures are determined. Technical parameter are taken from of Daikin Altherma catalogue. Electrical consumptions at different air temperatures and and partial loads are calculated with RC World 5 program. In addition, an auxiliary heater is added for air source heat pump to support the equipment especially for cold climates. For horizontal ground source heat pump, entering water temperatures are calculated by depending on outside air temperatures for heating and cooling seasons. Ground source heat pump technical parameters are taken from Canovate company. Electrical consumptions are determined for ground source heat pump in partial loads and different entering water temperatures. In addition a circulation pump is defined for ground side water circulation. Maximum and minimum entering water temperature values for ground source heat pump are taken from the manufacturer. Energy bills are also calculated from the hourly simulation program by entering the electrical and fuel rates. These rates are taken from Turkish Statistical Institution. Annual energy consumptions of three mechanical systems are calculated for five different climate zones in Turkey. In all climate zones heat pump systems are decreased the energy consumption and CO2 emissions significantly compared to combi boiler and multi split air conditioning system. For heating and domestic hot water production, air source heat pump and ground source heat pump are consumed %80 and %84 less energy in comparison with combi boiler system. These ratios are obtained %78 and %82 respectively in the second degree-day region. In the third climate zone air source heat pump decreased the energy consumption by %65 and ground source heat pump decreased the energy consumption %82 in heating and domestic hot water production. In fourth and fifth degree day zones, air source heat pump decreased the energy consumption respectively by %50 and %18 when compared to combi boiler. On the other hand, ground source heat pump consumed %13 less energy in fourth region and %63 less energy in the fifth climate region for heating and domestic hot water production in comparison with combi boiler. As the heating degree days become higher and climate zone become colder, energy conversation of air source heat pump is decreaseddue to longer defrost times. For cooling, air source heat pump has reached maximum energy conservation in the second degree day zone by %28. The minimum energy conversation from air source heat pump is obtained inthe fifth climate region by %9. In the first, third and fourth climate regions, energy consumption for cooling decreased by %22, %24 and %18 respectively. For horizontal ground source heat pump, maximum energy conservation is obtained in the third climate zone by %57. The minimum energy conservation is obtained the fourth climate zone by %29. In the first,second and fifth climate zones, energy consumptions for cooling are decreased by %42, %43and %44 respectively. When the CO2 emissions are compared with each other for each degree day zone, it is obtained that in all regions except fifth one, heat pumps decreased the CO2 emissions of reference system. Thus the fifth region is the coldest climate of Turkey and auxilary heater consumes much electrical energy, CO2 emissions of air source heat pump is obtained higher than the reference combi boiler and multi split system. In the first climate zone, air source heat pump and horizontal ground source heat pump decreased the annual CO2 emissions respectively %36and %52 in comparison with reference system. In the second climate zone, these ratios are obtained as %40 and %52. For the third climate zone, ground source heat pump decreased the CO2 emissions of combi boiler and multi split system by %60 which is the two times of air source heat pumps performance. In the fourth climate zone, %14 and %30 CO2 emission decrese are obtained from air source heat pump and ground source heat pump respectively, when compared with reference system.In the final climate zone ground source heat pump decreased the CO2 emissions %32 however air source heat pump increased the emissions by %21. For the economical analysis, the initial investment and maintenance costs are taken directly from the manufacturers. When considered initial investments and annual energy bills together, it is obtained that air source heat pump is a good alternative mechanical system when compared to wall mounted combi boiler and multi split air conditioning system for first and second climate regions. For the third climatic region, payback periods of both air source heat pump and ground source heat pump are close to each other. Due to higher energy conversation and lower CO2 emissions, horizontal ground source heat pump can be a better alternative system. In the fouth climatic region, although CO2 emissions and annual energy bills of both heat pumps are lower than combi boiler and multi split alternative because of the high payback periods, both air source and horizontal ground source heat pump does not seem feasible investments. For the fifth climatic region, higher annual energy bills are obtained from air source heat pump alternative in comparison to combi boiler multi split alternative. So air source heat pump is not feaseble in terms of technically and economically. Even thogh horizontal ground source heat pump has lower annual energy bills and lower CO2 emissions, it is not seemed to be a good a good choice by economically due to it's high payback period.
Identification Of Optimum Mechanical System İn A Residential Building For Different Climate Zones Of Turkey
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Enerji Enstitüsü, 2018
Thesis (S.M.)--Massachusetts Institute of Technology, Dept. of Physics, [DATE]
Keywords: Enerji tüketimi; Mekanik tesisat; Sürdürülebilir enerji; Energy consumption; Mechanical applications; Sustainable energy